Clinical expression and mitochondrial deoxyribonucleic acid study in twins with 14484 Leber’s hereditary optic neuropathy: A case report - Chuenkongkaew W.L. (2023)
This study aimed to explore clinical and molecular factors that cause discordance for clinical expression of Leber’s hereditary optic neuropathy (LHON) in a pair of identical twins with the 14484 point mutation. CASE SUMMARY Twin patients with the 14484 point mutation were studied for zygosity by using the Short Tandem Repeats Typing system. For the monozygotic twins, the radioactive restriction and densitometric analyses were used to quantitate the heteroplasmy level for the 14484 point mutation. The mitochondrial genome was analyzed to determine influential factors by mitochondrial deoxyribonucleic acid (DNA) sequencing, denaturing high-performance liquid chromatography and next generation sequencing. For the dizygotic twins, the nuclear DNA was analyzed. The twins with 14484 LHON were monozygotic with homoplasmy. No difference in the point mutation in mitochondrial DNA was found. No modifying genes that potentially influenced the disparity in phenotypic expression of LHON were detected in these twins. CONCLUSION This 11-year follow-up of monozygotic twins showed additional genetic modifications and epigenetic factors are possibly associated with discordance for LHON.